2015
DOI: 10.1123/tsp.2014-0027
|View full text |Cite
|
Sign up to set email alerts
|

Cohesion and Performance for Female and Male Sport Teams

Abstract: A previous meta-analysis examining the relationship between cohesion and performance (Carron, Colman, Wheeler, & Stevens, 2002) revealed that this relationship was significantly stronger for female teams as compared with male teams. The purpose of the current study was to explore perceptions of the cohesion-performance relationship by coaches who have led teams of both genders. Semistructured interviews were employed with Canadian and German coaches with previous experience leading both male and female spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 0 publications
3
33
0
7
Order By: Relevance
“…Results showed that on large football teams, subgroups emerged as members identified with offensive or defensive units. The authors and other researchers (e.g., Carron, 1982;Eys et al, 2014) noted that subgroups (i.e., those that emerge from a team's structural design) and cliques (i.e., tight-knit emergent subgroups built upon reciprocal relationships; for a review, see Martin, Bruner, Eys, & Spink, 2014) can damage the formation of a cohesive team. Accordingly, it may thus be important for researchers to consider the existence of subgroups and cliques and whether group norms vary between those subgroups and other operationalizations of group size (e.g., dress or team roster).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Results showed that on large football teams, subgroups emerged as members identified with offensive or defensive units. The authors and other researchers (e.g., Carron, 1982;Eys et al, 2014) noted that subgroups (i.e., those that emerge from a team's structural design) and cliques (i.e., tight-knit emergent subgroups built upon reciprocal relationships; for a review, see Martin, Bruner, Eys, & Spink, 2014) can damage the formation of a cohesive team. Accordingly, it may thus be important for researchers to consider the existence of subgroups and cliques and whether group norms vary between those subgroups and other operationalizations of group size (e.g., dress or team roster).…”
Section: Discussionmentioning
confidence: 98%
“…From reviewing the group dynamics literature regarding gender (e.g., Bruner & Spink, 2011;Carron et al, 2002;Deaux, 1976;Eys et al, 2014), it was predicted that adolescent female athletes would have stronger perceptions of group norms than adolescent males (Hypothesis 1).…”
Section: Factors Impacting Normsmentioning
confidence: 99%
See 1 more Smart Citation
“…Também foi relatada a importância de organizarem reuniões sociais fora do cenário esportivo formal, buscando influenciar positivamente na coesão da equipe e melhorar o desempenho no esporte. Eys et al (2015) buscaram explorar as percepções da relação coesão-desempenho por treinadores que lideraram equipes de ambos os sexos. Foram realizadas entrevistas semiestruturadas com treinadores canadenses e alemães com experiências anteriores, onde lideraram equipes esportivas masculinas e femininas.…”
Section: Tabelaunclassified
“…Numerous prior studies have been proven the positive and significant relationship between team cohesion and the performances of players (Alemu & Babu, 2012;Beal, Cohen, Burke, & McLendon, 2003;Brawley, Carron, & Widmeyer, 1993;Bray & Whaley, 2001;Carron & Chelladurai, 1981a;Carron, Bray, & Eye, 2002;Carron, Colman, Wheeler, & Stevens, 2002;Chang, Duck, & Bordia, 2006;Jacob & Carron, 1998;Manning, 2007;Murray, 2006;Mullen & Copper, 1994;Mohd Zainal & Rosli, 2012;Williams & Widmeyer, 1991;Eys, Ohlert, Evans, Wolf, Martin, Bussel, & Steins, 2015). Murray (2006) study analysis revealed significant relationship between team cohesion and performance.…”
mentioning
confidence: 94%